2017
DOI: 10.21470/1678-9741-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between High Red Cell Distribution Width and Systemic Inflammatory Response Syndrome after Extracorporeal Circulation

Abstract: ObjectiveCardiac surgical operations involving extracorporeal circulation may develop severe inflammatory response. This severe inflammatory response syndrome (SIRS) is usually associated with poor outcome with no predictive marker. Red cell distribution width (RDW) is a routine hematological marker with a role in inflammation. We aim to determine the relationship between RDW and SIRS through our study.MethodsA total of 1250 patients who underwent cardiac surgery with extracorporeal circulation were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…One study found that the RDW level was significantly higher in patients with severe autoimmune hepatitis than in those with mild liver inflammation [ 28 ]. Increased RDW was significantly associated with an increased risk of severe inflammatory response syndrome after cardiopulmonary bypass following cardiac surgery [ 29 ]. At 8 weeks after RYGB, the RDW level in obese women was significantly higher than that before RYGB [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found that the RDW level was significantly higher in patients with severe autoimmune hepatitis than in those with mild liver inflammation [ 28 ]. Increased RDW was significantly associated with an increased risk of severe inflammatory response syndrome after cardiopulmonary bypass following cardiac surgery [ 29 ]. At 8 weeks after RYGB, the RDW level in obese women was significantly higher than that before RYGB [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, RDW is a hematological parameter that reflects heterogeneity in red blood cell size, [5,6] and is reportedly associated with systemic inflammation. [7,8] Given the readily available nature of RDW, it may be more clinically useful than other markers. Furthermore, RDW has been used to distinguish iron deficiency anemia from thalassemia or other hemoglobinopathies, and recent studies have identified elevated RDW in cases of atherosclerosis, inflammatory diseases, and cancers, [22,23] which highlights the potential utility of RDW in CRC diagnosis and prognostication.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Elevated RDW values are associated with several types of anemias, as well as with certain liver disorders and systemic inflammation. [7,8] Recent studies have also indicated that RDW is associated with the development of several cancers, with potential diagnostic and prognostic value for esophageal cancer, multiple myeloma, and hepatocellular carcinoma. [911] However, there are scarce and inconsistent data regarding the diagnostic value of RDW in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study has also concluded that RDW was increased in patients with SLE [12,13]. Due to the effect of inflammatory cytokines, there is a release of premature erythrocytes into the circulation and a resultant increase in RBC distribution width [14]. Moreover, platelets play a major role in SLE pathogenesis and represent a great potential for novel biomarkers and drug development [15].…”
Section: Introductionmentioning
confidence: 98%